2007
DOI: 10.1124/jpet.107.120931
|View full text |Cite
|
Sign up to set email alerts
|

Identification of IKr and Its Trafficking Disruption Induced by Probucol in Cultured Neonatal Rat Cardiomyocytes

Abstract: The human ether-a-go-go-related gene (hERG) encodes a channel that conducts the rapidly activating delayed rectifier K ϩ current (I Kr ), which is important for cardiac repolarization. Mutations in hERG reduce I Kr and cause congenital long QT syndrome (LQTS). More frequently, common medications can reduce I Kr and cause LQTS as a side effect. Protein trafficking abnormalities are responsible for most hERG mutation-related LQTS and are recently recognized as a mechanism for druginduced LQTS. Whereas hERG traff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
116
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(124 citation statements)
references
References 31 publications
4
116
2
Order By: Relevance
“…open versus closed) and the total number of functional channels at the plasma membrane. Studies have shown that mutations in hERG or drugs can decrease the hERG density at the plasma membrane, leading to a diminished I hERG , which causes long QT syndrome (7,41). However, it is unknown how the density of hERG channels on the plasma membrane is regulated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…open versus closed) and the total number of functional channels at the plasma membrane. Studies have shown that mutations in hERG or drugs can decrease the hERG density at the plasma membrane, leading to a diminished I hERG , which causes long QT syndrome (7,41). However, it is unknown how the density of hERG channels on the plasma membrane is regulated.…”
Section: Discussionmentioning
confidence: 99%
“…Single cardiomyocytes were isolated from 1-day-old Sprague-Dawley rats of either sex using enzymatic dissociation methods as described previously (7). Cells were cultured in Dulbecco's modified Eagle's medium/Ham's F-12 medium (Invitrogen) with 10% FBS.…”
Section: Methodsmentioning
confidence: 99%
“…For electrophysiological experiments on transiently expressed channels, GFP cDNA (pIRES2-EGFP, Clontech) was co-transfected for selection of transfected cells. Cardiac myocytes were isolated from neonatal Sprague-Dawley rats using enzymatic dissociation as described previously (18).…”
Section: Methodsmentioning
confidence: 99%
“…hERG proteins display two distinct bands in the Western blot analysis: a mature fully glycosylated form in the plasma membrane with a molecular mass of 155 kDa and an immature coreglycosylated form with a molecular mass of 135 kDa (18,20). SGK1 or SGK3 overexpression significantly increased the expression of the mature hERG protein (155 kDa) but had no significant effect on the expression of the immature hERG protein (135 kDa) (Fig.…”
Section: Sgk1 and Sgk3 Increase Herg Expression In The Plasmamentioning
confidence: 99%
“…7) Nevertheless, assessment of hERG-blocking activity has been proven to be valid for the risk evaluation of a majority of drugs. [8][9][10] However, there are some drugs which have no acute effect on the hERG channel current, but induce QT prolongation and ventricular arrhythmia such as pentamidine, [11][12][13] probucol 14,15) and cardiac glycosides. 16) These drugs have been reported to inhibit the intracellular trafficking of the hERG channel to the cell membrane.…”
mentioning
confidence: 99%